2003
DOI: 10.1111/j.1365-2621.2003.tb14120.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Bovine Lactoperoxidase Activity in Skim Milk: Kinetic and Thermodynamic Analysis

Abstract: The effect of heat on lactoperoxidase activity in bovine milk was studied over a range of 68 to 76 °C. Values of residual enzymatic activity after different treatments were studied by kinetic analysis, obtaining D-values and the Z-value (3.1 °C). Denaturation of lactoperoxidase, measured by loss in activity, can be described as a 1st-order reaction. Rate constants were calculated, as was the energy of activation, which was 737.69 kJ/mol. Thermodynamic parameters were also calculated. The high value obtained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…This results in positive entropies of activation of denaturation, ΔS (D) , because the randomness or disorder is increased in the transition from ground state to the unstable intermediate state (U), but α-amylases from pearl millet had negative entropy which revealed that the enzyme was in more ordered state (Tables I and II). The negative values for change in entropy could have some implications which include; compactation of the protein, ordering of water molecules in the vicinity of the hydrophobic residues and possible aggregation during denaturation (Gummadi, 2003;Marin et al, 2003). A similar trend was observed in peroxidase, lipoxygenase and polyphenol oxidase from white yam (Eze et al, 2010) and xylanase from Aspergillus niger (Pal and Khanum, 2011) but the magnitude was higher in enzymes from white yam, showing that they undergo more aggregation and compactation during inactivation.…”
Section: Table I Summary Of the Thermoinactivation And Thermodynamicmentioning
confidence: 56%
See 1 more Smart Citation
“…This results in positive entropies of activation of denaturation, ΔS (D) , because the randomness or disorder is increased in the transition from ground state to the unstable intermediate state (U), but α-amylases from pearl millet had negative entropy which revealed that the enzyme was in more ordered state (Tables I and II). The negative values for change in entropy could have some implications which include; compactation of the protein, ordering of water molecules in the vicinity of the hydrophobic residues and possible aggregation during denaturation (Gummadi, 2003;Marin et al, 2003). A similar trend was observed in peroxidase, lipoxygenase and polyphenol oxidase from white yam (Eze et al, 2010) and xylanase from Aspergillus niger (Pal and Khanum, 2011) but the magnitude was higher in enzymes from white yam, showing that they undergo more aggregation and compactation during inactivation.…”
Section: Table I Summary Of the Thermoinactivation And Thermodynamicmentioning
confidence: 56%
“…In the present study, ΔH (D) values were found to be decreasing as the temperature increased (Tables I and II). The high values of the change in enthalpy of denaturation obtained for thermoinactivation of the α-amylases from pearl millet indicated that the enzyme would undergo a considerable change in conformation during denaturation (Marin et al, 2003). The fact that ΔH values decreased with increase in temperature reveals that less energy is required to denature the enzyme at high temperature (Bhatti et al, 2006).…”
Section: Table I Summary Of the Thermoinactivation And Thermodynamicmentioning
confidence: 93%
“…The observed change in ΔH° also indicated that enzyme in both states exhibited a considerable conformational change at higher temperatures. 31 The Gibbs free energy (ΔG•) of thermal unfolding apparently increased with increase in temperature but did not reveal large differences between free and immobilized enzyme forms. This indicated that the immobilization of PoXyn2 did not adversely affect its thermal unfolding at higher temperatures.…”
mentioning
confidence: 99%
“…Milk contains several proteins that constitute a nonspecific defense system against microorganisms, lactoperoxidase and lactoferrin being the most representative. 10,11) Those two proteins have different antibacterial mechanisms and are used for different purposes, lactoferrin in functional products and lactoperoxidase to preserve milk before heat treatment, in countries with poor hygienic conditions of storage.…”
mentioning
confidence: 99%